Asthma Control Test: Comparing Parent Proxy With Parent and Child Report for Children 6 to 12 Years. (April 2017) - duRivage, Nathalie; Ross, Michelle; Mayne, Stephanie L.; Suh, Andrew; Weng, Daniel; Grundmeier, Robert W.; Fiks, Alexander G.
We compared results of a modified version of the Asthma Control Test using parent proxy report (PP-ACT) with results reported by children and parents using the validated Childhood–Asthma Control Test (C-ACT). 104 parent-child dyads with a child aged 6 to 12 years with asthma were randomized to complete PP-ACT followed by C-ACT or C-ACT followed by PP-ACT. Scores ≤19 indicated uncontrolled asthma. We calculated sensitivity, specificity, positive predictive value, and negative predictive value for the PP-ACT in comparison with the C-ACT, and calculated concordance between the 2 scales. The PP-ACT had sensitivity of 86% and negative predictive value of 88% for detecting uncontrolled asthma. More than 75% of surveys were concordant (κ = 0.54, moderate agreement). Our results suggest that while the PP-ACT missed few children with uncontrolled asthma and may simplify reporting of asthma control in circumstances when child report is not feasible or creates barriers to survey receipt, limitations of proxy reporting should be considered.